IMPLEMENTASI POLITICAL PUBLIC RELATIONS DALAM PILIHAN PRESIDEN (PILPRES) 2014 - Umar - Farouk (Politeknik Negeri Semarang, 2016)
Presidential Election in 2014 has given us aclear picture of political culture growing incontempary Indonesian political condition.Many believe that the excessive competitionbetween the two presidential candidates(Joko Widodo and Prabowo Soebianto) werecaused by the low politics practised bypolitical parties. Many negative politicalactions were done to win the competition.Political parties were negatively perceived.Negative image of the political parties wasnot proportionally considered important bythose parties. They were not aware of theimportance of implementing appropriatepolitical public relations to construct theirimage. Positive image of the political partiescertainly in the long run will create politialbenefits. This article tries to give a snapshotof the matter.